Promoting social partnership in employee training : Germany country report - (:unkn) unknown (Institut der deutschen Wirtschaft Köln, 2018)
"Initial dual and upgrading vocational training in Germany is based on the consensus principle. The social partners are satisfied with the bipartite and tripartite dialogue. Based on the principle that the need of qualification is known best in the companies and their associations, subsidiarity plays an important role in employee training. Capital four is divided into six chapters, which describes the role of the social partners. The chapters deals with the anticipation and identification of skills needs, the mobilising resources, information, support and guidance, contribution to quality, transparency and efficiency, the recognition and validation of competences and qualifications and provision of learning." (Autorenreferat ; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; G 1.2.2.2 Soziale Sicherungssysteme; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; L 2.1.1 Informelles Lernen; I 2.1 Deutschland; Berufliche Weiterbildung; Weiterbildungsbeteiligung; Weiterbildungsfinanzierung; Sozialpartner; Früherkennung; Informelle Kompetenz; Bundesrepublik Deutschland